2005
DOI: 10.1017/s0317167100004510
|View full text |Cite
|
Sign up to set email alerts
|

Management of Chronic Subdural Hematoma: A National Survey and Literature Review

Abstract: Chronic subdural hematoma (SDH) in the elderly population is a common problem encountered in neurosurgical practice. The incidence of chronic SDH has been reported as 1.7 per 100,000/year. 1 Thus, in Canada (population = 32 million), we can expect approximately 550 individuals with chronic SDHs per year. The peak incidence occurs in the sixth and seventh decades to 7.4 per 100,000 in the 70-79 age group. 1 With a greater proportion of elderly individuals in Canada over the next decade, the incidence of chroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
117
0
8

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(126 citation statements)
references
References 19 publications
1
117
0
8
Order By: Relevance
“…Surgery is generally recommended when chronic subdural hematomas become symptomatic. The optimal surgical procedure, the use of a closeddrainage system, and modalities of post-operative management are under ongoing debate (1,3,9,12,14,25,34,37). Complications of surgery mainly include infection, acute hemorrhage, post-operative seizure, symptomatic hygroma, and symptomatic pneumocephalus (16,22,29).…”
Section: Introductionmentioning
confidence: 99%
“…Surgery is generally recommended when chronic subdural hematomas become symptomatic. The optimal surgical procedure, the use of a closeddrainage system, and modalities of post-operative management are under ongoing debate (1,3,9,12,14,25,34,37). Complications of surgery mainly include infection, acute hemorrhage, post-operative seizure, symptomatic hygroma, and symptomatic pneumocephalus (16,22,29).…”
Section: Introductionmentioning
confidence: 99%
“…5,15,19 Overall, BHC seems to be the most widely practiced technique, as it balances a lower recurrence rate (in comparison with TDC) with a lower morbidity rate (in comparison with craniotomy). 3,5,15,16,19 Nevertheless, continuing refinement and evaluation of existing surgical techniques is essential for improving the care and outcomes of patients with CSDH. More recently, a novel technique involving a hollow screw, which is threaded through a twist-drill hole in the cranium and is then connected to a closed drainage system, has been increasing in its popularity and use.…”
mentioning
confidence: 99%
“…Lately, twist drill craniostomy has been defined, but it is not frequently used as it is expensive, the related knowledge is not sufficient, and the first studies showed high recurrence rates (33%). 1,2,6 Although burr-hole craniostomy has been shown as a safe treatment method, reported relapse rates are between 9.2% and 26.5%. 7,8 For craniotomy, postoperative mortality rates mount to 11%, and morbidity rates mount to 25%.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of the disease is approximately 1-58/100 000, and the disease is most frequently seen in 70-80-year-old individuals. [1][2][3] Cortical atrophy and enlargement of potential subdural space increase subdural venous tension and create susceptibility to bleeding after trauma in elderly. Enlargement of subdural space also facilitates formation of membranes formed by blood degradation components after bleeding.…”
Section: K Ke Ey Y Wmentioning
confidence: 99%